Improving Writing Skills; An Implementation of “Think Pair Share” for Islamic Junior Schools Students - Suhrowardi Suhrowardi (Journal of Languages and Language Teaching, 2020)
The objectives of this study are to capture the implementation of Think Pair Share (TPS) in teaching-learning process, to identify the improvement of the students' writing skills, and to find out the strengths and the weaknesses of Think Pair Share (TPS) in the teaching-learning process of the seventh-grade students of MTS AL Islahuddin Kediri. This research is a classroom action research. The researcher used qualitative and quantitative data. The qualitative data was interview and observation. The quantitative data was tested. The step to analyze the qualitative data used data reducing, data display, and conclusion drawing. The step to analyze the quantitative data used mean formula. The result of the research shows that there are positive improvements in either student" writing skills or the class situation during the teaching-learning process.  It can be seen from the result of the test which is improved,  from the students" writing score and the post-test conducted after the action. The mean scores of students" writing scores are increased. Besides, the situation of the class is more conducive before implementing it. From the class situations improvement, it can be drawn some strengths and the weaknesses of the Think Pair Share (TPS) implementation in writing class. The strengths include that the Think Pair Share (TPS) can build critical thinking, motivation, classroom interaction, easy to discuss, -self-confidence, and active learners. The weaknesses are required special attention in classroom use, and it needs a mediator.